EVALUATING TELKOMSEL PROMOTIONAL MIX USING IMPORTANCE AND PERFORMANCE ANALYSIS - Walewangko, Aronnaldo Prince; Tumbuan, Willem J. F. A.; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: In this era Telecommunication and Promotion became important aspect. Promotion is very significant elements of marketing activities. All over the world, from the large multinational corporation to medium and even small firmsrecognize that there is no best alternative than promotion to communicate with customer and motivate them to purchase their products or services. On Promotional Mix there are variables within, which is: Advertising, Direct Marketing, Sales Promotion, Public Relation, Personal Selling. Every variable have their own indicators who will become the base of questioner that will be gave to the customers and to receive their feedback, about their thought about the importance and performance of Telkomsel Promotion in Manado. This research using Importance and Performance Analysis, and 100 respondents are the sample size of this research. The result of this study shows that window display placed in quadrant I (very important but low performance), in quadrant II (very importance and high performance) that shows the Sales Promotion, Public Relation, and Personal Selling in this position. While Advertising and Direct Marketing in Quadran III. So, related with the findings in this research, there is some recommendation for Telkomsel.Â Â Keywords: promotional mix, advertising, direct marketing, sales promotion, public relation, personal selling, importance and performance analysis